2020
DOI: 10.1016/j.toxcx.2020.100061
|View full text |Cite
|
Sign up to set email alerts
|

Envenoming by the rattlesnake Crotalus durissus ruruima in the state of roraima, Brazil

Abstract: The aim of this study was to evaluate the clinical-epidemiological factors associated with victims of rattlesnake envenoming in the state of Roraima, Brazil. In this location, rattlesnake accidents are caused by the subspecies Crotalus durissus ruruima . This is a prospective observational study carried out at the General Hospital of Roraima from april 2017 until july 2018. A total of 37 alleged rattlesnake victims had their medical records evaluated. However only one of them proved to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 36 publications
2
21
0
10
Order By: Relevance
“…Most of the snakebites occurred in the lower (85.6%) and upper limbs (13.1%) ( Table 2 ). This epidemiological profile confirms small case series previously published in the state of Roraima ( 25 , 26 , 115 ). Asato and colleagues showed that the C. ruruima envenomings attended to in Boa Vista, the capital of the state of Roraima, predominantly involved farmers during morning or afternoon work in their fields ( 26 ).…”
Section: Human Envenomations Caused By C D Ruruimasupporting
confidence: 91%
See 4 more Smart Citations
“…Most of the snakebites occurred in the lower (85.6%) and upper limbs (13.1%) ( Table 2 ). This epidemiological profile confirms small case series previously published in the state of Roraima ( 25 , 26 , 115 ). Asato and colleagues showed that the C. ruruima envenomings attended to in Boa Vista, the capital of the state of Roraima, predominantly involved farmers during morning or afternoon work in their fields ( 26 ).…”
Section: Human Envenomations Caused By C D Ruruimasupporting
confidence: 91%
“…In this situation, where the snake is partially covered by vegetation, its visual detection becomes more difficult ( 24 ). Thermoregulation constitutes the main diurnal activity of nocturnal Viperidae snakes ( 20 , 24 ), which may explain most cases of snakebite in Roraima state, since this period is also that of human activity in the area ( 25 , 26 ).…”
Section: Crotalus Durissus Ruruima : Natural Historymentioning
confidence: 99%
See 3 more Smart Citations